Program Kemitraan Masyarakat: Pemanfaatan Pangan Lokal sebagai Sumber Asupan Gizi bagi Balita Prasejahtera Daerah Perbatasan di Kabupaten Merauke - Adi Sumarsono; . Nurcholis; Sri Winarsih (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2019)
The phenomenon of children suffering from malnutrition in the Asmat Regency, Papua Province is still the subject of national media coverage and is one of the benchmarks of the government's success in implementing pro-people programs. This community partnership activity is intended to increase knowledge, understanding, and skills of the parents of pre prosperous families live in the border regions of the Republic of Indonesia/Papua New Guinea (RI/PNG) in processing and utilizing local food as a source of nutritional intake. Method of the activity consisted of: training and mentoring. The improvement program uses standard limits on eligibility and limits on achievement of change. The Community Partnership Program (PKM) has succeeded in increasing the knowledge and care of parents of pre-prosperous families for the nutritional needs of their sons and daughters, and improving the parents’ skills in growing local food using home yards. Increased skills can be seen from the results of the creativity of citizens in making food creations that are in accordance with the concept of adequate nutrition using local food.